Respuesta :

Answer:

The answer is B

Step-by-step explanation:

If u use calculator,u will get the ans as x¹=6 and x²= -2 but u have to change it to the opposite which means negatif to positive(-2=2) and positive to negative(6= -6).Hope u can understand...sorry,English isn't my first language

Answer:

x= 6 and x=-2

Step-by-step explanation:

find the two factors that when multiplied will get -12 and when summed up will get -4.

so -6 and 3

(xsquare-6) +(2x -12)=0

x(x-6)+2(x-6)=0

(x-6)=0 (x+2)=0

group like terms

x=6. x=-2

ACCESS MORE